The Use of Mobile Games in the Management of Patients With Attention Deficit Hyperactive Disorder: A Scoping Review - Jiang, Haowen; Natarajan, Rohit; Shuy, Yao Kang; Rong, Lim; Zhang, Melvyn Weibin; Vallabhajosyula, Ranganath (Frontiers in Psychiatry, 2022)
Attention deficit hyperactivity disorder (ADHD) is a common neurodevelopmental disorder associated with significant morbidity. Current treatment approaches consist of a mixture of pharmacological and psychological approaches. The emergence of digital technology, and mobile gaming applications, represents a promising novel method in potentially augmenting existing interventions for ADHD. In this review, we will map out the use of mobile gaming applications in the management of ADHD and evaluate the effectiveness of these technologies and any areas for future research. Four electronic databases were searched for relevant articles. All articles were screened for abstract and full text by two independent reviewers, and data was extracted onto a common data extraction sheet. The data was narratively synthesized and reported in line with the PRISMA guidelines. A total of 19 studies were included. Studies mostly evaluated the effectiveness of games on male children with ADHD. Most games were focused on the treatment of ADHD, while a minority were focused on the diagnosis and monitoring of ADHD. Some of the common gaming mechanisms employed in games included having participants responding to cures, remembering details, and making associations between different entities. The studies generally showed an improvement in the performance of children as they played the games, but evidence for the effectiveness of these modalities remains scarce and mixed. While it is exciting that there is such a wide variety of games available currently in the diagnosis, treatment, and monitoring of ADHD, many of the games lack clinical evidence to prove their effectiveness. Furthermore, most studies contain several limitations including small sample size, limited ages of participants, lack of control group, and lack of comprehensive outcomes. To promote the application of these games to clinical practice, robust clinical trials, collaboration between stakeholders, and using a comprehensive set of outcome measurements are essential.